Isentropic Compressibilities of Binary Mixtures of Methylcyclohexane with Substituted Benzenes and Cyclohexanone - Venkatesulu, D.; Prabhakara Rao, M.V. (Asian Journal of Chemistry, 2010)
Ultrasonic sound velocities for four binary liquid systems of methylcyclohexane with substituted benzenes and cyclohexanone have been determined at 303.15 K. The substituted benzenes include chlorobenzene, nitrobenzene and benzonitrile. Further, isentropic compressibilities (Ks) and deviation in isentropic compressibilities (ΔKs) have been computed from the sound velocity and density data derived from excess volumes. The results show that ΔKs are negative over the entire range of composition for all the binary systems studied. The observed values of ΔKs have been discussed in terms of existence of specific interactions between the components of various mixtures.